56. KNOWLEDGE, ATTITUDES AND PRACTICES RELATED TO HIV/AIDS OF NURSING STUDENTS AT VINH MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objective:  To describe the knowledge, attitudes and practices related to HIV/AIDS of nursing students at Vinh Medical University in 2024. Research subjects and methods: Cross-sectional descriptive study on 284 nursing students at Vinh Medical University from August 2024 to April 2025. Data were collected using a pre-prepared questionnaire, designed in the form of a survey for students to fill out themselves. Results: Of the total 284 students, the percentage of students with knowledge about HIV was 43.7%, with a total average score of 10.19±2.85. The percentage of students with positive attitudes was 48.9%. 53.9% of people think that they have the right to refuse to care for HIV patients. 49.3% of people wish they did not have to care for people with HIV. The percentage of students who do not choose to care for people with HIV is 49.3%. Students who practice safety account for 48.9%.Conclusion: The percentage of students with general knowledge, positive attitudes and good practices about HIV/AIDS are all below 50%. Schools should increase and update students' knowledge about HIV/AIDS.
Keywords: Knowledge, attitude, practice, nursing students, HIV/AIDS